Procalcitonin-Guided Antibiotic Therapy in Adult Sepsis: A Biochemical Perspective from a Retrospective Cohort Study: Biochemical Evaluation of PCT-Guided Sepsis Treatment - Zhang, Yi; Liu, Zhe; Ma, Chen; Wang, Wenjing; Chen, Wei (Journal of Medical Biochemistry, 2025)
Background: Procalcitonin (PCT), a biomarker closely associated with bacterial infections, has emerged as a valuable tool in guiding antibiotic therapy. In sepsis management, it may help optimize antibiotic use and improve clinical outcomes. This retrospective cohort study aimed to evaluate the effectiveness of PCT-guided antibiotic therapy in adult sepsis patients, with a particular focus on biochemical responses.Methods: We retrospectively analyzed medical records of 110 adult sepsis patients admitted between January 2019 and December 2023. Patients were allocated to either a standard antibiotic group (n=53) or a PCT-guided antibiotic group (n=57). Key variables included demographic data, treatment duration, infection control metrics, and laboratory parameters such as white blood cell (WBC) count, C-reactive protein (CRP), and PCT levels before and after therapy.Results: Compared to the standard group, the PCT-guided group exhibited significantly greater reductions in WBC, CRP, and PCT levels (P < 0.05), shorter antibiotic duration, fewer secondary infections, and improved antibiotic de-escalation rates. A higher complete response rate (17.54% vs. 3.77%) was also observed in the PCT-guided group. No significant difference was found in 28-day mortality.Conclusions: PCT-guided antibiotic therapy led to more favorable changes in key biochemical markers and clinical outcomes, supporting its role as a biomarker-driven approach to antibiotic optimization in sepsis management.
Keywords: Procalcitonin; Sepsis; Biomarkers; Antibiotic therapy; C-reactive protein; White blood cells; Retrospective study